PENGEMBANGAN KETERAMPILAN BERFIKIR IVENTIF PADA SISWA DALAM PROGRAM KELAS INSPIRASI (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThe issues of educational system and the lack of studentsâ skills have been a debated issue in several countries including Indonesia. Educational system is hoped to be able to educate students to have a lot of skills especially inventive-thinking skills of elementary school students. The aim of this study is to determine the inventive thinking in primary school students in a school in Pekanbaru at inspiration class. This research involves survey design. This research let us to collect data quickly for getting multiple issues and problems on various perspectives. The instruments used are questionnaire, interview and a module of inventive thinking skills development. The results show that elementary school students already have good skills in accordance with the level of class. The learning system at the elementary school is expected to pay attention to aspects of the development of these skills.Keywords: Issues, inventive-thinking skills and inspiration class.